Funkcjonowanie rynku usług w Polsce - Wiśniewski, Florian (Wydział Prawa i Administracji UAM, 1972)
The article suggests some changes in (the functioning of the service market in Poland. The subjects under consideration are maintenance, repairing and personal services from the aspect of planning and management, prices, wages, and ways of supply. It is suggested that planning and management should belong to the activities of the people's councils. The district people's councils might work out medium-range plans, where the investment plan would be one of the elements. This could become the basis to work out yearly assignments for single service enterprises. As it appears synthetic measures supplemented with natural ones may be most adequate because they control the correct trends of their activities. As regards prices the author suggests that (the number of services centrally controlled should be limited and prices should be seasonally changed to be adjusted to the fluctuation of demand. He proposes a formula depending on counting in profil, turnover tax and overhead costs according to the interest on fixed and working assets of the enterprise to direct costs (particularly wages). To secure quantitative and qualitative development of services it is necessary to employ such a system of wages that the earnings of skilled service workers may be as those in the other branches of then national economy or even higher. As regards the supply a general reform in the national economy is needed. A antralization of the stock record of the spare parts is necessary for a proper management. The author suggests that a bonus fund should be built out of the profits to increase an influence upon the extend and direction of economic activities of service enterprises. To make the enterprises take a greater interest in services rendered to the population the rate of turnover tax paid on those activities to the budget should be reduced.
Functioning of the Service Market in Poland (A Preliminary Model)